2011
DOI: 10.1111/j.1439-0272.2011.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacterial contamination of semen on sperm chromatin integrity and standard semen parameters in men from infertile couples

Abstract: A considerable proportion of male factor infertility cases are associated with inflammatory processes. The most common sexually transmissible agents causing sexually transmitted diseases in industrial countries are Chlamydia trachomatis, genital Ureaplasma and Mycoplasma spp. This study was undertaken to investigate whether these bacterial contaminants in semen affect sperm quality parameters and particularly DNA integrity (detected by sperm chromatin structure assay) in males from infertile couples (n = 293).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 60 publications
0
40
1
2
Order By: Relevance
“…However, Rybar et al concluded that the contaminated semen with C. trachomatis, Ureaplasma and Mycoplasma spp. were not associated with sperm DNA fragmentation (85).…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Rybar et al concluded that the contaminated semen with C. trachomatis, Ureaplasma and Mycoplasma spp. were not associated with sperm DNA fragmentation (85).…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 96%
“…The effect of the male genital tract infection depends on the pathogen type, acute or chronic condition as well as the site of infection, where the inflammation can occur in the epididymis, prostate gland or seminal vesicles (66). In certain situation the genital tract inflammation become difficult to diagnose because the symptoms may not be apparent (Asymptomatic infection) and the patients only suffering from some local discomfort (85).…”
Section: The Effects Of Bacterial Infection On Sperm Chromatin Condenmentioning
confidence: 99%
“…11 Certain types of bacteria, including Mycoplasma, Ureaplasma, Escherichia coli, and Chlamydia trachomatis, may be more harmful to sperm function than others. 11,12 Resistance patterns of bacteria in semen samples have not been frequently reported. In one study by Isaiah et al, semen samples of 140 men in Nigeria were examined, and 59% of the bacteria cultured were resistant to oxacillin.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, despite successful antibiotic therapy, semen quality parameters did not improve at least up to 3 months after the therapy. Sperm chromatin integrity assessed by the presence of DNA breaks was not seen with these infections [72]. Also, when looking at the prevalence of these infections, there was no difference comparing fertile to infertile couples [73].…”
Section: Urethritismentioning
confidence: 96%
“…It has been shown that the presence of elementary bodies of C. trachomatis serovar E within the lab setting caused a significant decrease in motile sperm with an increase of dead spermatozoa [60]. The detection of Chlamydia in either semen or urine has been associated with a reduction in sperm numbers [61], reduction of the percentage of progressively motile sperm [62][63][64][65], and abnormal morphology and viability [65].…”
Section: Chlamydia and Fertilitymentioning
confidence: 98%